College algebra - Sullivan, Michael (Boston, Massachusetts : Pearson Education, Incorporated, 2016)
This text provides a contemporary approach to college algebra, with three chapters of review material preceding the chapters on functions. This list places the features in their proper context, as building blocks of an overall learning system that has been carefully crafted over the years to help the student get the most out of the time they put in studying .